Q: Solve for P Q equals 30 - 2P?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

First, set up the equation you are given: 15 - 2p = 9 Subtract 15 from each side of the equation: 15 -2p - 15 = 9-15 Then, you should have: -2p = -6 Divide each side by -2: (-2p)/(-2) = (-6/-2) Solve for p: p = 3

P - - p = 2p

A*D*2P

p = 4

That depends what the value of p is.

Related questions

3p = 2p + 12 subtract 2p from both sides 3p - 2p = 2p - 2p + 12 1p = 12 p = 12 this is how you solve this problem.

You can combine like terms of p to get 6p. If you are given what p equals you can solve for the completely numerical answer.

2p+10 = 8p-14 2p-8p = -14-10 -6p = -24 p = 4

It equals 2p because p+p=2p.

You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.

First, set up the equation you are given: 15 - 2p = 9 Subtract 15 from each side of the equation: 15 -2p - 15 = 9-15 Then, you should have: -2p = -6 Divide each side by -2: (-2p)/(-2) = (-6/-2) Solve for p: p = 3

no. you would solve and get -80=-2p or 80=2p. thus resulting in p=40

p^2 - 2p - 3 = 0 p^2 - 2p = 3 halve the linear term (-2), square it and add it to both sides p^2 - 2p + 1 = 3 + 1 factor left, gather terms right (p - 1)^2 = 4 (p - 1)^2 - 4 = 0 (1,-4) are the vector points of this parabola You can factor to solve for p (p + 1)(P - 3) p = - 1 p = 3

If: 2p+5r = q Then: p = (q-5r)/2

P - - p = 2p

8p+4=6p+10 8p-6p=2p 10+4=14 2p=14 p=7

-3+4p-2p=1 -3+2p=1 2p=4 p=2